CCAR1 and CCAR2 as gene chameleons with antagonistic duality: Preclinical, human translational, and mechanistic basis. Issue 10 (9th August 2020) - Johnson, Gavin S.; Rajendran, Praveen; Dashwood, Roderick H.
Abstract: Cell Cycle and Apoptosis Regulator 1 (CCAR1) and Cell Cycle and Apoptosis Regulator 2 (CCAR2) have emerged as key players in physiology and pathophysiology, with critical roles in the DNA damage response, nuclear receptor function, and Wnt signaling, among other activities. Contradictory reports exist on the functional duality of CCAR1 and CCAR2 as either tumor promoters or suppressors, suggesting that CCAR1 and CCAR2 have the hallmarks of gene chameleons. We review herein the mechanistic, preclinical, and human translational findings for CCAR1 and CCAR2, based on available RNA and protein expression data from human studies, The Cancer Genome Atlas (TCGA) data mining, gene knockout mouse models, and cell‐based assays. Multiple factors contribute to the divergent activities of CCAR1 and CCAR2, including tissue type, mutation/genetic background, protein‐protein interactions, dynamic regulation via posttranslational modifications, and alternative RNA splicing. An array of protein partners interact with CCAR1 and CCAR2 in the context of tumor promotion and suppression, including β‐catenin, androgen receptor, p21 Cip1/Waf1, tumor protein p53 (p53), sirtuin 1, and histone deacetylase 3. Genetic changes frequently found in cancer, such as TP53 mutation, also serve as critical determinants of survival outcomes in cancer patients. This review seeks to provide the impetus for further investigation into CCAR1 and CCAR2 as potential master regulators of metabolism, aging, and cancer. Abstract : Cell cycle and apoptosis regulator 1 (CCAR1) and CCAR2 have emerged as key players in physiology and pathophysiology, with important roles in Wnt signaling, nuclear receptor function, adipogenesis, and the DNA damage response. Due to the diverse array of protein partners, including beta‐catenin, androgen receptor, p21, p53, sirtuin 1, and histone deacetylase 3, literature reports exist on the functional duality of CCAR1 and CCAR2 as either tumor promoters or suppressors. Genetic changes frequently found in cancer, such as TP53 mutation, also serve as critical determinants of patient survival outcomes and impact the roles of CCAR1 and CCAR2 as master regulators of metabolism, aging, and cancer.